2005
DOI: 10.1152/ajpgi.00226.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CFTR by ASBT-mediated bile salt absorption

Abstract: In cholangiocytes, bile salt (BS) uptake via the apical sodium-dependent bile acid transporter (ASBT) may evoke ductular flow by enhancing cAMP-mediated signaling to the cystic fibrosis transmembrane conductance regulator (CFTR) anion channel. We considered that ASBT-mediated BS uptake in the distal ileum might also modulate intestinal fluid secretion. Taurocholate (TC) induced a biphasic rise in the short circuit current across ileal tissue, reflecting transepithelial electrogenic ion transport. This response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 53 publications
1
31
2
Order By: Relevance
“…Using whole-cell current recording, we found that 0.1 mmol/L of CDC did not activate CFTR and therefore conclude that stimulation of CFTR does not underlie the effect of CDC of the anion exchanger. Our data contrast with the results of Bijvelds et al, 24 who found that luminal administration of 0.5 mmol/L of taurocholate did stimulate CFTR-dependent electrogenic Cl j transport in the murine ileum. These contrasting results may be due to differences in species and tissues and the type and concentration of bile acids used.…”
Section: Discussioncontrasting
confidence: 99%
“…Using whole-cell current recording, we found that 0.1 mmol/L of CDC did not activate CFTR and therefore conclude that stimulation of CFTR does not underlie the effect of CDC of the anion exchanger. Our data contrast with the results of Bijvelds et al, 24 who found that luminal administration of 0.5 mmol/L of taurocholate did stimulate CFTR-dependent electrogenic Cl j transport in the murine ileum. These contrasting results may be due to differences in species and tissues and the type and concentration of bile acids used.…”
Section: Discussioncontrasting
confidence: 99%
“…In the small intestine, these differential species-dependent effects are not so well characterized, but they certainly differ from those in the colon. For instance, CDCA is a relatively poor secretagogue in the ileum [110][111][112][113] . It should be noted that ileal BA absorption is electrogenic, even in the absence of chloride/bicarbonate secretion, due to the 2:1 stoichiometry of ASBTmediated Na + :BA symport [111,114,115] .…”
Section: Effect Of Ba On Ion Transportmentioning
confidence: 99%
“…This pertains to the actions of BAs in the large intestine, since T84 cells have a colonic epithelium phenotype. More recently, BA were described to induce ion secretion via transactivation of the cystic fibrosis transmembrane conductance regulator (CFTR) [113] . CFTR is the main chloride/bicarbonate channel in intestinal epithelial cells and is pivotal to ion secretion in the gastrointestinal tract, among other tissues.…”
Section: Effect Of Ba On Ion Transportmentioning
confidence: 99%
See 2 more Smart Citations